Anti-immunoglobulin-like transcript 3 induced acute myocarditis—A case report - Itzhaki Ben Zadok, Osnat; Shiyovich, Arthur; Hamdan, Ashraf; Yeshurun, Moshe; Nardi Agmon, Inbar; Raanani, Pia; Kornowski, Ran; Shargian, Liat (Frontiers in Cardiovascular Medicine, 2022)
To the best of our knowledge, this is the first published report of anti-immunoglobulin-like transcript 3 (ILT3)-induced myocarditis. A 48-year old female patient with refractory acute myeloid leukemia who was given a single dose of anti-ILT3 monotherapy presented with fever, hypotension, chest pain, and elevated cardiac biomarkers. Systolic bi-ventricular function was in normal limits. The patient was promptly treated with pulse dose steroids with a rapid hemodynamic and clinical improvement and declining levels of cardiac biomarkers. The diagnosis of acute myocarditis was confirmed using cardiac magnetic resonance imaging applying the revised Lake Lewis criteria. While larger-scale data are needed in order to assess the incidence, management and prognosis of anti-ILT-3 induced myocarditis, we believe a high level of suspicion for adverse non-target cardiac effects is required in patients receiving this novel class of drugs.